Study on the recycle of steel slag as an adsorbent for COD removal in pulp mill wastewater - Trinh Van Tuyen; Do Van Manh; Nguyen Tuan Minh; Pham Thi Doan; Tap, Van Huu; Viet, Trinh Minh (Vietnam Journal of Science and Technology, 2022)
This study aims to characterize and investigate steel slag for the removal of its persistent organic pollutants (measured as COD) from pulp mill wastewater. Steel slag and its NaOH-modified states were characterized by Fourier-transform infrared spectroscopy (FT-IR), Brunauer-Emmett-Teller (BET) surface area analysis, Barrett-Joyner-Halenda (BJH) pore size, and volume analysis. Batch adsorption experiments were conducted to investigate the COD adsorption of slag-based adsorbents. The modification of NaOH was found to improve the COD adsorption capacity (by 1.5 times) of steel slag by generating hydroxyl and carboxyl groups and enlarging the specific surface area and pore size in the steel slag particles. In batch experiments, the suitable conditions for COD adsorption on NS (steel slag) and MS20 (2 M NaOH-modified steel slag) were determined to be pH 6 - 8, contact time 90 minutes, and adsorbent dosage 20 g/L. Langmuir and Freundlich adsorption isotherm models satisfactorily described the adsorption of COD on both NS and MS20 with a good correlation. According to the Langmuir isotherm, the maximum COD adsorption capacity of NS and MS20 were 5.16 and 6.87 mg/g, respectively. Column experiments demonstrated that NS and MS20 had promising potential for COD treatment in pulp mill effluent. According to the column results, 20 g of NS or MS20 was able to keep 300 mL or 525 mL of 125 mg/L COD wastewater, respectively, reaching the threshold of the National Technical Regulation on Industrial Wastewater QCVN 40:2021/BTNMT.